Optimization of a rice cooking method using response surface methodology with desirability function approach to minimize pesticide concentration - Medina, María Belén (2021)
Rice is contaminated with pesticides applied in pre and post-harvest. These contaminations could be reduced through household operations like washing and cooking. Therefore, in the present research, a pre-soaking rice cooking method was used to reduce pesticides residues. Response Surface Methodology with Central Composite Design was applied to minimize pesticides concentration by choosing the best soaking time and water:rice grain relation before cooking. A quadratic polynomial equation was obtained. Desirability function approach gave the optimal cooking conditions as 14 h soaking time and water:rice grain relation of 3. This process allowed a pesticide elimination of 100.0 %, 93.5 %, 98.4 %, 98.5 %, 99.0 %, and 95.0 %, of azoxystrobin, cyproconazole, deltamethrin, epoxiconazole, kresoxim-methyl and penconazole, respectively.